Bootstrap Methods in Econometrics - James G. MacKinnon (Queen's University, Department of Economics, 2006)
There are many bootstrap methods that can be used for econometric analysis. In certain circumstances, such as regression models with independent and identically distributed error terms, appropriately chosen bootstrap methods generally work very well. However, there are many other cases, such as regression models with dependent errors, in which bootstrap methods do not always work well. This paper discusses a large number of bootstrap methods that can be useful in econometrics. Applications to hypothesis testing are emphasized, and simulation results are presented for a few illustrative cases.
Keywords: C12; C15; 330; bootstrap; Monte Carlo test; wild bootstrap; sieve bootstrap; moving block bootstrap